Math, asked by ADITYAPSPK9, 1 year ago

solve
(1) log10 (x + 5) = 1
(ii) log10 (x + 1) + log10 (x - 1) = log1011 + 2 log103​

Answers

Answered by yadaiahakki1976
0

Answer:

1) x= 5 ( log base10 10) = 1

Answered by MissSolitary
1

 \underline{ \underline{{ \huge{ \mathtt{Q}}} \sf UESTION   \: - }}

Solve:

 \sf \: (i) \:  log_{10}(x + 5)  = 1

 \sf \: (ii) \:  log_{10}(x + 1)  +  log_{10}(x - 1)  =  log_{10}(11)  + 2 log_{10}(3)

 \underline{ \underline{ { \huge{ \mathtt{A}}} \sf  {NSWER - }}}

We know that,

 \blue{ \sf{ : \implies{ log_{a}(a) = 1 }}}

 \sf \: i) \:  log_{10}(x + 5)  =  log_{10}(10)  \\  \sf  \implies \: x + 5 = 10 \\  \sf \implies \: x = 10 - 5 \\ \boxed{ \red{  \sf \implies \: x = 5}}

we know that,

 \blue{ \sf{ : \implies{ log_{a}(b)  +  log_{a}(c) =  log_{a}(b \times c)  }}} \\  \blue{ \sf{ :  \implies{2 log_{a}(b)  =  log_{a}( {b}^{2} ) }}}

 \sf \: ii) \:  log_{10}(x + 1) (x - 1) =  log_{10}(11)  +  log_{10}( {3}^{2} )  \\  \sf \implies \:  log( {x}^{2}  + 1)  =  log(11 \times  {3}^{2} )  \\  \sf \implies \:  log( {x}^{2}  - 1)  =  log(11 \times 9)   \\  \sf \implies \:  {x}^{2}  - 1 = 99 \\  \sf \implies {x}^{2}  = 99 + 1 \\   \sf \implies \:  {x}^{2}  = 100 \\  \sf \implies \: x =  \sqrt{100}  \\  \boxed{ \red{ \sf \implies \: x = 10}}

_____________________________

@MissSolitary✌️

________

Similar questions